НАЦИСТСЬКА ЕЛІТА НА ОКУПОВАНИХ ПОЛЬСЬКИХ ЗЕМЛЯХ (Zaporizhzhia Historical Review, 2021)
The article is devoted to the analysis of the conditions and peculiarities of the activities of the Nazi elite on the ethnic Polish lands. According to the research, which is based on the original documents and materials, it is proved that top representatives of the German management staff on Polish lands such as G.Frank, A.Forster and A.Graizer greatly influenced on the development and features of Nazi ìnew orderî in occupied Poland.